MODERN MANAGER QUALITIES (Journal of Universal Science Research, 2024)
In this article, the leader is the person responsible, responsible for what the qualities of the personnel should be, what is the need to focus on in the management of personnel, from the big problems of the leadership team to the success of zarraday. The leader is an elegant employee who has a reputation in the community, who can follow people with his attitude, attitude. The leader has the ability to influence the members of the team, there has been talk of uniting the members of the team.